(untitled) (Revista Diálogos, 2017)
Neste trabalho, traçamos uma narrativa sobre a introdução do pensamento de Bakhtin no Brasil. Para tanto, realizamos um pesquisa bibliográfica e exploratória. Observamos que a obra do pensador ficara um longo período desconhecida, sendo mais amplamente difundida a partir de 1960. Ainda assim, no contexto brasileiro, a ditadura militar foi a principal força que silenciou os estudos de Bakhtin. Isso, porém, não o tornou de todo esquecido: por meio, sobretudo, de seus artigos na imprensa e de suas aulas ministradas na Pós-Graduação, Boris Schnaiderman foi um dos principais estudiosos que, durante esse período, difundiu os estudos de Bakhtin. In this paper, we trace a narrative on the introduction of the thought of Bakhtin in Brazil. To this end, we conducted a bibliographical and exploratory research. We note that this thinker’s work had been unknown for a long period, being more widely diffused from the 1960 decade. Still, in the Brazilian context, the military dictatorship was the primary force that silenced the Bakhtin studies. That, however, didn’t make him at all forgotten: particularly through his articles in periodicals and his lectures in postgraduate courses, Boris Schnaiderman was one of the leading scholars who, during this period, spread the studies of Bakhtin.